(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The scores onperceived intensity of pain and perceived frequency of attack scale were takenas baseline scores. For the second phaseof the study a sample of seventy five patients was selected. Only those patients having at least twoattacks in a fortnight period and scored three or more on a five point scale onthe perceived intensity of pain scale were selected for psychologicalintervention. But some patients weredropped out in between and only sixty patients were remaining for intervention.These sixty patients were randomly assigned to the three groups. Thus, therewere twenty participants in each of the three groups. The three groups wererandomly assigned to three treatment condition. One group was given Jacobson progressivemuscular relaxation training (JPMR). The second group was given EMG-biofeedbacktraining and the third group was taken as the control group. The participants in the JPMR relaxation groupwere given relaxation training as designed above in every alternative day forfifteen days. Similarly, the participants in EMG-biofeedback group were alsogiven training for every alternative day for fifteen days.